PET imaging of prostate tumors with 18F‐Al‐NOTA‐MATBBN. (14th April 2014) - Pan, Donghui; Yan, Yongjun; Yang, Ronghua; Xu, Yu Ping; Chen, Fei; Wang, Lizhen; Luo, Shineng; Yang, Min
<x xml:space="preserve">Abstract</x> Overexpression of the gastrin‐releasing peptide receptor (GRPR) in prostate cancer provides a promising target for detection the disease. MATBBN is a new bombesin analog originating from the GRPR antagonists with a hydrophilic linker. In this study NOTA‐conjugated MATBBN was labeled by the Al18F method and the potential of 18F‐Al‐NOTA‐MATBBN for prostate tumor PET imaging was also evaluated. NOTA‐MATBBN was radiolabeled with 18F using Al18F complexes. Partition coefficient, in vitro stability and GRPR binding affinity were also determined. PET studies were performed with 18F‐Al‐NOTA‐MATBBN in PC‐3 tumor‐bearing mice. 18F‐Al‐NOTA‐MATBBN can be produced within 30 min with a decay‐corrected yield of 62.5 ± 2.1% and a radiochemical purity of >98%. The logP octanol–water value for the Al18F‐labeled BBN analog was −2.40 ± 0.07 and the radiotracer was stable in phosphate‐buffered saline and human serum for 2 h. The IC50 values of displacement for the 18F‐Al‐NOTA‐MATBBN with MATBBN was 126.9 ± 2.75 nm. The PC‐3 tumors were clearly visible with high contrast after injection of the labeled peptide. At 60 min post‐injection, the tumor uptakes for 18F‐Al‐NOTA‐MATBBN and 18F‐FDG were 4.59 ± 0.43 and 1.98 ± 0.35% injected dose/g, and tumor to muscle uptake radios for two tracers were 6.77 ± 1.10 and 1.78 ± 0.32, respectively. Dynamic PET revealed that 18F‐Al‐NOTA‐MATBBN was excreted mainly through the kidneys. GRPR‐binding specificity was also demonstrated by reduced tumor uptake of 18F‐Al‐NOTA‐MATBBN after coinjection with excess unlabeled MATBBN peptide at 1 h post‐injection. NOTA‐ MATBBN could be labeled rapidly with 18F using one step method. 18F‐Al‐NOTA‐MATBBN may be a promising PET imaging agent for prostate cancer. Copyright © 2014 John Wiley & Sons, Ltd.